Synthesizing A Framework and Establishing Content Validity of An Energy Literacy Instrument for Indonesian Students - Usman, Musawwir; Pramudawardani, Hanis; Umam, Rofiqul; Takahashi, Hirotaka (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Energy literacy is a critical competency for cultivating awareness, responsibility, and sustainable energy practices among students. This study aims to synthesizing a framework and establishing the content validity of an instrument designed to measure Indonesian students’ energy literacy across cognitive, affective, and behavioral domains. Employing a descriptive research design, the study was conducted in two stages: framework synthesis and expert validation. The synthesized framework integrated key constructs from established energy literacy models and contextualized them within Indonesia’s socio-educational setting. The initial instrument comprised 32 cognitive test items, 20 affective statements, and 15 behavioral statements. Content validation was performed by two expert lecturers and three science teachers, who assessed the relevance, clarity, and appropriateness of each item. Results indicated that all domains achieved the “very feasible” category, demonstrating strong content validity. Following revisions based on expert feedback, 59 items were retained: 30 cognitive, 17 affective, and 12 behavioral. The validated instrument offers a comprehensive and contextually relevant tool for evaluating students’ knowledge, attitudes, and behaviors toward energy, thereby supporting the advancement of energy education and sustainable practices in Indonesia.